2020
DOI: 10.1021/acs.jctc.0c00374
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Method for Modeling Polarons Using Electronic Structure Methods

Abstract: Polarons are localized electronic states that occur in many semiconductors. Modeling polarons at the quantum or atomic scale is often performed using electronic structure methods such as density functional theory (DFT). A problem using DFT to model polarons is that selfinteraction errors (SIEs) often result in delocalized electronic states rather than localized states. Methods such as DFT + U or hybrid functionals can be used to overcome SIE, but these methods may still not form stable polarons. The initial ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 129 publications
(241 reference statements)
4
58
0
Order By: Relevance
“…As shown recently in a separate study, this approach is highly efficient for obtaining ground state structures of polarons. 58 We then linearly interpolate between the initial and final geometries to define a one-dimensional reaction coordinate for polaron hopping …”
Section: Methodsmentioning
confidence: 99%
“…As shown recently in a separate study, this approach is highly efficient for obtaining ground state structures of polarons. 58 We then linearly interpolate between the initial and final geometries to define a one-dimensional reaction coordinate for polaron hopping …”
Section: Methodsmentioning
confidence: 99%
“…Proton-coupled electron transfer (PCET) processes comprise the most fundamental elementary steps of important (photo)­electrocatalytic reactions such as oxygen reduction, CO 2 reduction, and water splitting. On semiconductor surfaces, the pH-dependent redox potentials and band-edge energies of many metal oxides imply that redox processes for these materials are coupled to proton transfer. Moreover, the thermochemistry of interfacial PCET may be impacted by proton-induced defects at the band edges or trap states within the band gap. PCET thermochemistry can be described in terms of bond dissociation free energies (BDFEs), which are commonly applied as descriptors for electrocatalytic reactions such as hydrogen evolution. The X–H BDFE, where X is a surface atom, corresponds to the reaction free energy for homolytic bond dissociation, X–H → X • + H • . BDFEs can be determined experimentally either from electrochemically measured proton-coupled redox potentials or by analyzing reaction equilibria in the presence of PCET oxidants with known BDFEs. , On the surface of metal oxides, however, the BDFEs of O–H bonds often depend on the oxidation states of the metal and oxygen surface ions. , Understanding the interplay between proton-coupled defects (i.e., electronic defects due to adsorbed H) and PCET thermochemistry has broad implications for metal oxide catalysis and electrocatalysis.…”
mentioning
confidence: 99%
“…Generation of a bias initial guess wave function in such a way is a helpful method to study a polaron at a specific site on the lattice. [ 55 ] Deskins and Dupuis showed that both rutile and anatase can form electron polarons and reduce the oxidation state of Ti +4 to Ti +3 at the polaron trapping site. [ 52 ] The formed electron polaron can then migrate to a neighboring Ti +4 ion via a hopping mechanism.…”
Section: Widely Used First‐principles Methods To Study Polaronsmentioning
confidence: 99%